"The Rock I Cling To": Religious Engagement in the Lives of Life-Sentenced Women. (September 2014) - Dye, Meredith Huey; Aday, Ronald H.; Farney, Lori; Raley, Jordan
A growing body of research—much of which has focused on male inmates—suggests that religion ameliorates many pains and problems of imprisonment. The purpose of this study is to examine the effects of religious engagement on prison adjustment among a sample of 214 females serving life sentences in a Southern state prison system. Results of multivariate analyses indicate that religious engagement is indirectly related to prison adjustment; however, the role that religious engagement plays seems to be through helping women deal with feelings of depression. Women's personal accounts of prison adjustment corroborate these findings.